Malagueira’s Notebooks: A Reading on the Relevance of Drawing for Architectural Research - Guilherme, Pedro (2022)
Álvaro Siza Viera began in March 1977 the constant, methodical, and continuous, almost compulsive, recording of drawings in A4 notebooks. This record, which spans over the 22 years he spent working at the Bairro da Malagueira project in Évora, allows us to understand his conception and design process, and reflects the ability of drawing to serve as a tool for investigation through design. This type of record, far beyond the record of the real usually made in a travel notebook, constitutes an essential testimony of the author and his work, but also of architecture and its conception process. The research used 48 notebooks dedicated to Malagueira and presents the indications of a research process centered in the observation and design of the territory and in the imagination of its future as a basis for the progressive construction of an urban plan, of its moments and elements. Based on this knowledge it is possible to affirm the character of drawing to bring together elements from the field of history and architecture that are close to the place and the themes of the ongoing project. Drawing brings together the possibilities of the transformation of this memory at the service of the present in the construction of the future and the architectural project.